Use of Oral Sodium Phosphate Colonic Lavage Solution by Canadian Colonoscopists: Pitfalls and Complications - A Chan; W Depew; S Vanner (Canadian Journal of Gastroenterology)
Oral sodium phosphate (NaP) has become an attractive alternative to polyethylene glycol (PEG) for colonic cleansing before colonoscopy, but it potentially has greater complications. This study surveyed members of the Canadian Association of Gastroenterology (CAG) to determine how these colonic lavage agents are used and what complications have been encountered. The Dillman survey technique produced responses from 67% of the 400 members who perform colonoscopy. For the larger out-patient group, respondents used NaP more frequently than PEG (46% versus 35%, respectively, P<0.015). Respondents used NaP and PEG with similar frequencies for the in-patient group (44% versus 43%). Of respondents using NaP, 45% reported excluding its use in patients with renal failure, 30% with heart disease, 13% with incomplete bowel obstruction and 9% with extreme age. Symptoms suggestive of hypovolemia were reported in 9% of those using NaP compared with 3% using PEG (P<0.02). Three patients receiving NaP developed acute renal failure. A greater proportion of those using NaP had small unexplained aphthous ulcers (16%) and excessive luminal bubbling (24%) compared with PEG users (3%, P<0.00001 and 14%, P<0.03, respectively). These data demonstrate that members of CAG use NaP more frequently than PEG as the colonic lavage solution before colonoscopy. A greater number reported complications with NaP versus PEG, and a significant proportion of the respondents appeared to be unaware of the potential for these complications in specific clinical circumstances.